Dynamic construction of lattice of cuboids in data warehouse. Issue 6 (17th August 2020) - Mann, Suman; Phogat, Ajay Kumar
Abstract: In the field of Business Intelligence we require quick and efficient analysis of multidimensional data. Data warehouse (DW) and Online analytical processing (OLAP) approaches have been developed for this purpose which represents data in the form of cuboids. Lattice structures have been developed which consists of data cubes or cuboids. In the Lattice framework base cuboid contains all N - dimensions and moving up to the hierarchy we reach to 0 - Dimensional cuboid called apex cuboid. New cuboid may be generated by roll-up through dimension reduction. Dimension of cuboid may be reduced and increase according to business requirement. In this paper an algorithm is proposed for constructing cuboid dynamically. Cuboid are need to select in all ways for materialization purpose. Dynamic construction of cuboid enables materialization in fast and efficient way.